S Studi Farmakovigilans Vaksinasi Booster Covid-19 Pada Masyarakat Di Desa Pujon Kalimantan Tengah: Studi Farmakovigilans Vaksinasi Booster Covid-19 Pada Masyarakat Di Desa Pujon Kalimantan Tengah - Norlita, Devi; Yuwindry, Iwan; Aryzki, Saftia; Melviani, Melviani (LPPM Universitas Sari Mulia, 2024)
Background: Covid-19 booster vaccination is expected to achieve herd immunity (group immunity) forming antibodies or strong immunity so that people can survive the Covid-19 virus and hopefully the Covid-19 pandemic will turn into a Covid-19 epidemic. Adverse Drug Reactions (ROM) are unwanted side effects of a drug that arise when administering the drug at a dose used for prophylaxis, diagnosis, and therapy that is actual or potential.Objective: To determine the Pharmacovigilance Study of Covid-19 booster vaccination in the Pujon Village community, Central Kalimantan.Method: This study is Observational in nature, Quantitative. with a descriptive research method, the approach used in this study is cross-sectional. The study was conducted in July in the Pujon Village environment, Central Kalimantan.Results: From the side effects of the Covid-19 booster vaccination, namely the results of the Naranjo Algorithm measurement, it is known that out of 98 respondents, the Pujon village community received the most results in the Naranjo Probable category, which is a side effect of the Covid-19 vaccination, with 20 respondents (20.41%). It is known that there were 55 respondents who experienced possible side effects. Among them, 25 had fever and 30 had pain after receiving the Covid-19 vaccination.Conclusion: From the side effects of the Covid-19 booster vaccination, namely the results of the Naranjo Algorithm measurement, it is known that out of 98 respondents, the Pujon village community received the most results in the Naranjo Possible category, which is a possible side effect of the Covid-19 vaccination, with 55 respondents (56.12%). It is known that there were 55 respondents who experienced possible definite side effects. Among them, 25 had fever and 30 had pain after receiving the Covid-19 vaccination